2019
DOI: 10.1021/acs.jced.8b01004
|View full text |Cite
|
Sign up to set email alerts
|

Densities and Viscosities for the Ternary System of Decalin + Methylcyclohexane + Cyclopentanol and Corresponding Binaries at T = 293.15 to 343.15 K

Abstract: Densities (ρ) and viscosities (η) for the ternary system of decalin (1) + methylcyclohexane (2) + cyclopentanol (3) and three corresponding binary systems have been measured over the whole composition range at 11 temperature points from 293.15 K to 343.15 K under atmospheric pressure (0.1 MPa). The excess molar volumes (V m E ) and viscosity deviations (Δη) of binary systems have been calculated and further fitted with the Redlich−Kister equation, while corresponding physical data of the ternary system have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 35 publications
(34 reference statements)
1
11
0
Order By: Relevance
“…Accepted theories suggested that the reasons for the variations of V m E values can be divided into three aspects: (1) chemical intermolecular forces (i.e., hydrogen bond); (2) physical intermolecular forces (i.e., van der Waals forces); and (3) structural effects (i.e., geometrical interstitial accommodation). …”
Section: Resultsmentioning
confidence: 99%
“…Accepted theories suggested that the reasons for the variations of V m E values can be divided into three aspects: (1) chemical intermolecular forces (i.e., hydrogen bond); (2) physical intermolecular forces (i.e., van der Waals forces); and (3) structural effects (i.e., geometrical interstitial accommodation). …”
Section: Resultsmentioning
confidence: 99%
“…There are three reasons for the variations of V m E values: (1) physical intermolecular forces (i.e., van der Waals forces), (2) chemical intermolecular forces (i.e., hydrogen bonds), and (3) structural effects (i.e., geometrical interstitial accommodation). …”
Section: Resultsmentioning
confidence: 99%
“…As economic and environmental problems have become increasingly serious due to excessive consumption of petroleum fuels, considerable attention has been paid to exploiting different sustainable energy sources to replace traditional petroleum fuels. , Among those alternatives, biofuels have attracted extensive attention in light of their low pollution, small production costs, and renewability. , Biofuels, composed of long-chain methyl or ethyl monoesters, are produced from the transesterification of any biomass with a short-chain alcohol such as methanol or ethanol . In addition to being used as a solitary fuel, biofuels can also act as oxygenated additives to improve the combustion performance of aviation fuels. , Recently, many research studies about biofuels as fossil fuel additives have been carried out. Arkoudeas observed that the addition of sunflower and olive oil to the JP-8 aviation fuel could significantly reduce the emission of particulate matters. Chuck investigated the compatibility of nine potential biofuels with Jet A-1 aviation kerosene, and the result showed the lubricity properties of mixtures were tremendously improved compared with the single fuel.…”
Section: Introductionmentioning
confidence: 99%